Activation of LSCF–YSZ interface by cobalt migration during electrolysis operation in solid oxide electrolysis cells. (9th November 2022) - Shen, Jian; Miao, Bin; Liu, Qinglin; Wu, Yongfeng; Chan, Siew Hwa; Zhong, Zheng; Pan, Zehua
Abstract: High-temperature water electrolysis through solid oxide electrolysis cells (SOEC) will play a key role in building a hydrogen economy in the future. However, the delamination between the air electrode and the electrolyte remains a critical issue to be addressed. Previously, it was hypothesized that Co migration may improve the catalytic activity of the SrZrO3 second phase at the LSCF-YSZ interface, eventually leading to the delamination. In this work, the LSCF-YSZ interfaces sintered at different temperatures were examined in detail. The activation behaviors of the LSCF electrodes upon application with electrolysis current were characterized under different conditions. Further, samples containing purposely added SrZrO3 interlayer with and without cobalt were fabricated and compared. The activation process is less significant for the sample with cobalt-added SrZrO3 interlayer than the sample with pure SrZrO3 layer, supporting the hypothesis that Co migration may lead to the activation behavior. Graphical abstract: Image 1 Highlights: LSCF-YSZ interface was examined thoroughly using SEM and XRD for SrZrO3 formation. Electrolysis current was applied on LSCF electrode to study the activation behavior. Higher current density or sintering temperature causes more significant activation. Two samples were fabricated containing SrZrO3 layers with and without cobalt. Co-added SrZrO3 hinders the activation, associating the activation to Co migration.